2015
DOI: 10.1007/s13201-014-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimization of coagulation and flocculation process

Abstract: Natural coagulants have been the focus of research of many investigators through the last decade owing to the problems caused by the chemical coagulants. Optimization of process parameters is vital for the effectiveness of coagulation process. In the present study optimization of parameters like pH, dose of coagulant and mixing speed were studied using natural coagulants sago and chitin in comparison with alum. Jar test apparatus was used to perform the coagulation. The results showed that the removal of turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(76 citation statements)
references
References 24 publications
3
63
0
2
Order By: Relevance
“…The dangling grafted chains on the polysaccharide backbone, due to increased flexibility, could easily approach the contaminants. Saritha et al showed that sago starch is very efficient in removal of color, turbidity, alkalinity, and hardness compared to alum …”
Section: Applications Of Grafted Sago Starchmentioning
confidence: 99%
“…The dangling grafted chains on the polysaccharide backbone, due to increased flexibility, could easily approach the contaminants. Saritha et al showed that sago starch is very efficient in removal of color, turbidity, alkalinity, and hardness compared to alum …”
Section: Applications Of Grafted Sago Starchmentioning
confidence: 99%
“…This is because polymeric organic coagulants are effective at a wide range of pH (Vedoy and Soares, 2015). Although the coagulant dosage was found to be the most influential factor, under-dose or overdose can hinder the objective of reducing the cost associated with chemical usage or improving water quality (Saritha et al, 2015). In this case, the pH and the flotation time were kept at constant optimum conditions of 5 and 15 min, respectively.…”
Section: Response/water Quality Modelsmentioning
confidence: 99%
“…This occurred via the mechanism of flocculation of the oil droplets and the repulsion between the oil droplets and air bubbles (Saritha et al, 2015).…”
mentioning
confidence: 99%
“…In 2017, a few studies focused on some natural materials as treatment aids since they rarely need processes, and are less harmful than industrial chemicals. Saritha et al (2017) examined chitin and sago as coagulants for turbidity removal as compared with alum, which found that the natural coagulants had a better ability to deal with seasonal variance in turbidity than alum.…”
Section: Coagulation/flocculationmentioning
confidence: 99%